Radical Innovation Process in Sustainable Development and Knowledge Management: Toyota Prius Case Study. Issue 1 (January 2021) - Tomlins, Richard; Malynka, Oksana; Sukumar, Arun; Rao, Mimi; Pandya, Kaushik
Abstract: This article looks at the inter-linkages and causalities between innovation and knowledge management in terms of sustainable development goals through the case study method. Taking the case of the Toyota Prius, these concepts are further developed in detail. Recognising the fact that no organisational process can happen in a vacuum and that there are a host of extraneous factors that have a significant impact on the process, factors such as culture, vision, incentives are also examined here. Further, this article delves into some of the characteristics that successful organisations display and seeks to extrapolate from the specific to general implications for organisations that aim to be successfully innovative.